The Study of Electrical Description for Non-Thermal Plasma Needle System - Abbas, Ibrahim Karim; Hussein, Mohammed Ubaid (Iraqi Journal of Science, 2021)
In this research, a non-thermal plasma system was designed and a non-thermal plasma needle was manufactured for argon gas operating at normal atmospheric pressure. The electrical description of this system studied by using two different values of voltages (4.9,8) kV. Where the results showed the small amount of electrical current consumed by the system of plasma needle up to several microns of amps, and the value of the electrical current increase with the increasing gas flow, as well as the results, showed that happen a breakdown voltage at (8) kV when gas flow (4 l/min) causing a slight decrease in the electrical current value.